2015
DOI: 10.1111/and.12407
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between donor sperm parameters and pregnancy outcome after intrauterine insemination: analysis of 2821 cycles in 1355 couples

Abstract: The aim of this study was to investigate whether sperm parameters can affect the pregnancy outcome of artificial intrauterine insemination with cryopreserved donor spermatozoon (AID). A total of 1355 couples received 2821 AID treatment cycles in the Reproductive Medicine Center of the Tongji Medical College between January 2010 and December 2013, and the data were collected and retrospectively analysed. The relationship between pre-freezing, post-thawing as well as optimised sperm parameters and AID pregnancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Song et al [13] reported that the cumulative pregnancy rate increased with the number of cycles used, reaching 41.1% after 3 cycles. Guan et al [14] also observed a progressive increase in cumulative live birth rate to a value of 24.9% after 5 cycles, with no further improvement after additional treatment cycles. Other research also supports the use of multiple AID treatment cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Song et al [13] reported that the cumulative pregnancy rate increased with the number of cycles used, reaching 41.1% after 3 cycles. Guan et al [14] also observed a progressive increase in cumulative live birth rate to a value of 24.9% after 5 cycles, with no further improvement after additional treatment cycles. Other research also supports the use of multiple AID treatment cycles.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the recovery results of frozen sperm have improved with the development of cryopreservation technology (Li et al 2010;Valcarce et al 2013;Saeednia et al 2016)). However, most studies have focused on clinical pregnancies resulting from frozen donor sperm (Chen et al 2012;Zarek et al 2014;Kop et al 2015;Guan et al 2016). The objective of our study was to determine the association between frozen donor sperm used for IUI and clinical and neonatal outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Ferrara et al (2002) and De Brucker et al (2009) concluded that ovarian stimulation did not significantly improve pregnancy rates and delivery rates. Numerous sperm parameters have also been suggested as possible predicting factors, ranging from prefreezing sperm motility (Guan et al, 2015), to post-thaw sperm motility (Clarke et al, 1997), forward progression (Freour et al, 2009;Kelly et al, 1997), inseminating motile count (IMC) (Kang and Wu, 1996;Williams and Alderman, 2001;Zuzuarregui et al, 2004) and total motile sperm counts (TMSC) (Dong et al, 2011;Freour et al, 2009). Many studies, however, were unable to detect such relationships (Clarke et al, 1997;Ferrara et al, 2002;Guan et al, 2015;Kang and Wu, 1996;Kelly et al, 1997;Sidhu et al, 1997).…”
Section: Introductionmentioning
confidence: 99%